2010 35th IEEE Photovoltaic Specialists Conference 2010
DOI: 10.1109/pvsc.2010.5615877
|View full text |Cite
|
Sign up to set email alerts
|

Impact of materials on back-contact module reliability

Abstract: This paper discusses the impact of several combinations of encapsulants, conductive adhesives and back-sheet foils on ECN's back-contact modules performance and reliability. Damp-heat (85˚C; 85% R.H) and thermal cycling (-40˚C; +85˚C) tests were performed up to twice as long as described in the IEC-61215 standard, i.e. 2000 hours of damp-heat and 400 thermal cycles. These tests have been identified as the most important tests for this technology. After climatic chamber testing, the modules were analyzed visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The introduction of a new module technology based on a back-sheet foil with an integrated conductive grid in combination with conductive adhesive raises issues in terms of the reliability of the concept. Recent studies carried out on small-size (single and four cells) and full-size (6×10 cells) modules pointed at a prominent impact of dimensional and functional stability of the conductive back-sheet foil on the module reliability [5,6]. Guichoux et al [5] pointed at an interaction between encapsulant and ILD in the presence of moisture causing delamination and ultimately module failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of a new module technology based on a back-sheet foil with an integrated conductive grid in combination with conductive adhesive raises issues in terms of the reliability of the concept. Recent studies carried out on small-size (single and four cells) and full-size (6×10 cells) modules pointed at a prominent impact of dimensional and functional stability of the conductive back-sheet foil on the module reliability [5,6]. Guichoux et al [5] pointed at an interaction between encapsulant and ILD in the presence of moisture causing delamination and ultimately module failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies carried out on small-size (single and four cells) and full-size (6×10 cells) modules pointed at a prominent impact of dimensional and functional stability of the conductive back-sheet foil on the module reliability [5,6]. Guichoux et al [5] pointed at an interaction between encapsulant and ILD in the presence of moisture causing delamination and ultimately module failure. Eerenstein et al [6] have reported on MWT modules successfully passing TC300, DH2000, and the wet leakage test.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that epoxy-based conductive adhesive is applied in back contact solar cell module technology which especially features with its low shading coverage on the cell surface and an optimization of electrical design by minimizing the string/encapsulation loss [10][11][12]. The conductive adhesive has a low curing temperature which beneficially reduces cell breakage during interconnecting, and the literature reveals the back contact solar module pass the thermal cycling for 200 times [13]. However, the low acceptance in the replacement of conductive adhesive in solar cell stringing is restricted to the lack of confidence in the reliability and unfamiliarity.…”
Section: Introductionmentioning
confidence: 99%